FORMULATION AND EVALUATION OF SUBLINGUAL TABLET OF LOSARTAN POTASSIUM - Kumar, Damit; Sharma, Amit; Garg, Rajiv (Asian Journal of Pharmaceutical Research and Development, 2018)
The objective of the current study was to develop and optimize a sublingual tablet of Losartan potassium, which is an effective drug in the treatment of hypertension. Owing to number of advantages dissociated with the quick onset of action and it by passes the liver. Sublingual tablets offer effective and easier way for management of Hypertension. The basic approach used in development of Sublingual tablet was the use of super disintegrants by direct compression method. Oral mucosal drug delivery is one of the promising method of systemic drug delivery which offers several advantages. The literal meaning sublingual is ''under the tongue''. Hence the method includes the administrating drug via mouth so that it is absorbed via blood vessels (systemic) present under the tongue. Sublingual tablet is tablet that dissolves or disintegrates in the oral cavity without need of drinking water. Sublingual tablet traditionally have been used as an effective method to improve the dissolution properties and bioavailability of water-soluble drugs. In the preformulation studies, Losartan potassium was characterized by its physiochemical properties such as melting point, solubility, partition coefficient, UV and FTIR studies. UV spectroscopic method was established for quantitative estimation of the drug and the absorbtion maxima were 234 nm. The tablets were formulated by using the direct compression technique. The post compression studies i.e. shape, size, weight variation, hardness, friability and wetting time determined the quality of the product. Key words:-Sublingual, oral cavity, mucous, bioavailability, Gland, Losartan potassium, Systemic, Solubility.